Development of ZnO@rGO nanocomposites for the enzyme free electrochemical detection of urea and glucose. Issue 6 (19th August 2020) - Babitha, K. B.; Soorya, P. S.; Peer Mohamed, A.; Rakhi, R. B.; Ananthakumar, S.
Abstract : Development of ZnO@rGO based nonenzymatic urea and glucose sensors. Abstract : Herein, we report a green synthetic strategy for the preparation of ZnO@rGO nanocomposites. Bioinspired synthesis of ZnO nanoarchitectures has been done using a series of biotemplates such as dextrose, sucrose, soluble starch, and carboxy methyl cellulose. The as-prepared morphologically tuned ZnO nanoarchitectures are homogeneously distributed over the surface of rGO sheets, resulting in the formation of ZnO@rGO nanocomposites. For the first time, zinc (Zn) dust, a waste byproduct from industry (Binani Zinc Limited, Kerala, India), is employed for the chemical reduction of GO. ZnO@rGO nanocomposite based nonenzymatic urea and glucose sensors have been developed over a glassy carbon electrode, and the electrochemical performance of the nanocomposite for the detection of urea and glucose are investigated. The biosensor electrode is sensitive to urea in the concentration range of 0.02 × 10 −3 mM to 7.2 × 10 −3 mM with a detection limit of 0.012 μM. When used for glucose detection, the linear range is 0.02 × 10 −3 mM to 18 × 10 −3 mM, with a detection limit of 0.008 μM. The developed sensor exhibits an ultra-high sensitivity of 682.8 μA mM −1 cm −2 towards urea and 481 μA mM −1 cm −2 towards glucose.